Effect of Steeping Syzygium aromaticum L. Leaves on The Acceleration of Healing of Rattus norvegicus Burns - Adrien Jems Akiles Unitly; Welmince T. Luarwan (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2020)
This study aims to determine the effect of clove leaf steeping (Syzygium aromaticum L.) on the repair of burns of Rattus norvegicus rats. Samples were 12 rats and were divided into 4 groups. Each group was given clove leaf steeping at a dose of 0.09g / species/ day, 0.18g / species / day, 0.36g / species / day, and the control group. Samples were adapted for a week, then treated for 14 days. The results showed a burn repair that was also shown statistically between the length and width of burns of Rattus norvegicus mice. It was concluded that administration of clove leaf steeping (Syzygium aromaticum L.) was able to accelerate the healing of Rattus norvegicus rat burns, with the most effective dose being 0.36g.